In-Process Inventories and Multiproduct Production Systems. - Corcoran, A. Wayne; Leininger, Wayne E. (The Accounting Review, 1973)
Abstract The article discusses how in-process inventories could be incorporated into a quantitative planning model for multiproduct production systems, in reference to an article written by Gerald A. Feltham in the January 1970 issue of the periodical "The Accounting Review." By determining first a standard transfer cost, costing of inventories is facilitated. The article explains that the standard transfer cost i is equal to the standard cost of all resources required preceding a unit of activity in process i. It is possible to employ standard costs in costing the in-process inventories of the production system.